2002
DOI: 10.1590/s0100-67622002000400012
|View full text |Cite
|
Sign up to set email alerts
|

Análise cinética da cura de adesivos de taninos das cascas de três espécies de Eucalyptus por calorimetria diferencial exploratória (DSC)

Abstract: O objetivo deste trabalho foi analisar a cinética de cura de adesivos à base de taninos de Eucalyptus grandis, Eucalyptus saligna e Eucalyptus urophylla por calorimetria diferencial exploratória (DSC), comparando-a com a cinética de cura de adesivos comerciais: fenol-formaldeído e de taninos de acácia-negra (Acacia mollissima D.Wild). Verificou-se que o adesivo de taninos de Eucalyptus urophylla apresentou os parâmetros cinéticos (energia de ativação, entalpia, temperatura de pico e ordem de reação) mais próxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…Some studies have shown that it is possible to work with solid content for tannin-based adhesive with values of 40 to 55%. MORI, et al [29] studied values of 55% for mixtures of adhesives and tannins removed from the bark of the black wattle; In the present study, it was observed that the Eucalyptus grandis tannins were significantly different from those obtained with other species.…”
Section: Evaluation Of the Properties Of Polyphenols And Adhesive Agentsmentioning
confidence: 39%
See 2 more Smart Citations
“…Some studies have shown that it is possible to work with solid content for tannin-based adhesive with values of 40 to 55%. MORI, et al [29] studied values of 55% for mixtures of adhesives and tannins removed from the bark of the black wattle; In the present study, it was observed that the Eucalyptus grandis tannins were significantly different from those obtained with other species.…”
Section: Evaluation Of the Properties Of Polyphenols And Adhesive Agentsmentioning
confidence: 39%
“…The coconut tannin presents an acidic pH value, which is already a characteristic of the tannic extracts. MORI et al [29] found pH values below 5 for eucalyptus and black wattle tannin adhesives. Phenol formaldehyde has an alkaline (basic) pH.…”
Section: Evaluation Of the Properties Of Polyphenols And Adhesive Agentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Aproximadamente 1 min antes da análise no DSC, adicionaram-se 10% de formaldeído sobre o teor de sólidos dos adesivos. Os termogramas foram obtidos da temperatura ambiente até 250 ºC, com taxa de aquecimento de 5, 10 e 15 o C/ min, conforme descrito por Mori (2002). Após as análises das três temperaturas, foram obtidos os parâmetros cinéticos.…”
Section: Methodsunclassified
“…Finalmente, a expressão que relaciona potencial zeta "ζ" e mobilidade eletroforética "µ e "é dada por: [ Pizzi, 1994;Mori, 2002;Trugilho, 2003] Apresenta funcionalidade "ajustável" podendo ser aplicado no controle de resíduos poluentes no tratamento de água, no curtimento de couro, na indústria alimentícia, farmacêutica, em corantes têxteis, dentre outros. A quitosana é obtida a partir da desacetilação parcial da quitina, ( inerte, insolúvel e extraída da carapaça de crustáceos ).…”
Section: Potencial Zetaunclassified